2012
DOI: 10.1177/0022034512452885
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Remineralizing and Anticaries Agents in Caries Management

Abstract: They summarized the state of the science and set a research agenda for the future for two key components of caries management, namely, antibacterial agents and remineralizing agents. Following that conference and the resulting publication, much work was done around the world, some published and some unpublished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 23 publications
0
35
0
3
Order By: Relevance
“…14 The presence of fluoride at the tooth surface prevents demineralisation of the dental enamel and encourages remineralisation.…”
Section: Fluoride Varnishmentioning
confidence: 99%
“…14 The presence of fluoride at the tooth surface prevents demineralisation of the dental enamel and encourages remineralisation.…”
Section: Fluoride Varnishmentioning
confidence: 99%
“…2 The average depth and area of groups A and B had no statistically significant differences prior to treatment. In the demineralizing solution, the concentrations of calcium and phosphate were saturated, therefore causing less damage to the enamel surface and creating the conditions for the formation of lesions in the enamel subsurface.…”
Section: 3mentioning
confidence: 88%
“…24,No. 2,[45][46][47][48][49] authors have identified the benefits of the morphological changes of teeth in different conditions.…”
Section: Using Scanning Electron Microscopy (Sem) Manymentioning
confidence: 99%
See 2 more Smart Citations